Proceso de ASC - TECNICAS ANALOGICAS PARA LA ESCULTURA Y LA HOLOGRAFIA (2023)
The proposed project in the semillero involves creating sculptures using holograms, under the guidance of an artist specializing in this field. Despite previous work with synthetic and digital techniques, there is a deliberate focus on analog holography to provide new group members with an opportunity to explore this technique. This approach aims to familiarize students with holography and encourage their creative development and teamwork skills.